Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/20503121221131691
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pattern and drug-related problems among colorectal cancer patients at oncology center in Ethiopia: A hospital-based study

Abstract: Objective: Despite the fact that cancer patients are highly susceptible to drug-related problems due to the effects of cytotoxic agents, data are limited due to a lack of studies on those patients. Hence, we aimed to investigate drug-related problems among patients diagnosed with colorectal cancer. Method: A registry-based cross-sectional study was conducted on colorectal cancer patients at the Felege Hiwot Comprehensive Specialized Hospital. Socio-demographic and disease-related characteristics, treatment reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 67 publications
2
17
0
8
Order By: Relevance
“…Drug–drug interactions, adverse drug reactions and the need for additional drug therapy were the most common DRPs among colorectal cancer patients. 41 Likewise, adverse drug reactions, the need for additional drug therapy, and dosing problems were the predominant categories of DRPs among colorectal cancer patients in our study setting. This high prevalence of adverse drug reactions in colorectal cancer patients could probably be related to the frequent use of chemotherapy-based regimens in managing this condition.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Drug–drug interactions, adverse drug reactions and the need for additional drug therapy were the most common DRPs among colorectal cancer patients. 41 Likewise, adverse drug reactions, the need for additional drug therapy, and dosing problems were the predominant categories of DRPs among colorectal cancer patients in our study setting. This high prevalence of adverse drug reactions in colorectal cancer patients could probably be related to the frequent use of chemotherapy-based regimens in managing this condition.…”
Section: Discussionmentioning
confidence: 70%
“…24,[38][39][40] In contrast to the study conducted in Ethiopia, we found a significantly higher prevalence of DRPs in our patients with colorectal cancer. 41 However, a Turkish study revealed a similar prevalence of DRPs among colorectal cancer patients after the first course of chemotherapy. 42 This could probably be linked to the frequent use of chemotherapy in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations